The Effect of Managerial Ownership, Research & Development, Financial Risk, and Investment on Firm Growth: The Mediating Role of Leverage in the Defense Systems Industry in Asia - Azizah , Kumiko; Usman, Bahtiar; Mustafa, Matrodji (Cita konsultindo, 2026)
This study examines the effects of managerial ownership, research and development (R&D), financial risk, and investment on firm growth in the Asian defense systems industry, with leverage serving as a mediating mechanism. The defense sector is characterized by heightened geopolitical exposure, persistent technological innovation requirements, and stringent risk governance, making the identification of firm-level growth drivers particularly critical(Gheorghe & Panazan, 2024).Using a balanced panel dataset of 74 defense systems firms operating across Asia over the observation period, this study applies panel data regression based on the Fixed Effects Model (FEM), complemented by mediation analysis to assess the indirect role of leverage(Sommet, 2025).The empirical findings indicate that managerial ownership and investment exert positive and statistically significant effects on firm growth. R&D intensity also demonstrates a positive association with firm growth, underscoring the strategic importance of innovation in sustaining competitive advantage within the defense industry(Nel et al., 2025). In contrast, financial risk does not show a significant impact on firm growth, suggesting the presence of effective risk management and institutional buffering mechanisms in defense firms. Moreover, leverage partially mediates the relationships between R&D and firm growth as well as between investment and firm growth, while its mediating role in other relationships is not statistically supported(Xia & Wei, 2025). This study offers novel empirical evidence by explicitly modeling leverage as an internal financial transmission mechanism linking innovation and investment to firm growth within a strategically regulated defense industry an aspect that remains underexplored in prior growth and capital structure literature(Wu et al., 2025). By focusing on Asian defense systems firms, this research extends existing evidence beyond conventional manufacturing or civilian high-technology sectors. The findings contribute to a more nuanced understanding of growth dynamics in defense-related industries and provide policy-relevant insights into ownership design, innovation financing, and financial governance under geopolitical constraints(Anderson & Luiz, 2025).